Conversation and change : integrating information literacy to support learning in the New Zealand tertiary context : a thesis presented for partial fulfilment of the requirements for the degree of Doctor of Philosophy at Massey University, Manawatu - Feekery, Angela Joy (Massey University, 2013)
This thesis outlines a participatory action research (PAR) PhD project aimed at embedding information literacy development into a four-year Bachelor of Environmental Planning (BEP) at a New Zealand university. The research suggests enhancing information literacy is an effective strategy to support students’ development of essential academic competencies over the full undergraduate programme. The research took an ‘informed learning’ (Bruce, 2008a) approach (using information to learn), shifting the focus of information literacy development from the library into the academic classroom. PAR allowed a dual focus on both action (to support staff to change pedagogy) and research (to understand the process of change). The key purpose of this research was to support BEP instructors to identify ways they could embed IL development into their curriculum and assessment to support students’ learning during the transition into and through tertiary study. This involved reconceptualising students’ apparent lack of effective research and writing skills as a developmental concern. Prior to this research, existing information literacy support in the Bachelor of Environmental Planning had an information search and retrieval focus. Furthermore, product-focused assessment did not explicitly engage students in key aspects of the research and writing process. Therefore, this research took a learner-focused, process-oriented view of learning, and developed a thread of reflective learning throughout the programme. To support quality source selection and use, library workshops were refocused and new formative assessments were created requiring students to justify source selection and reflect on learning. While the interventions proved successful in supporting learning, the research revealed that more in-depth conversation with academics, librarians and students on how information impacts on learning is needed to encourage students to make considered information choices and become informed learners.
Keywords: Information literacy; Tertiary education; Academic competency; Informed learning; University curricula